The Effect of Deficit Irrigation on Dry Matter Partitioning, Mobilization and Radiation Use Efficiency of Common Bean (Phaseolus Vulgaris L.). Issue 3 (4th February 2020) - Karimzadeh Soureshjani, Hedayatollah; Nezami, Ahmad; Kafi, Mohammad; Tadayon, Mahmoudreza
ABSTRACT: Two common bean genotypes were subjected to non-drought stress (NDS), moderate drought stress (MDS), and severe drought stress (SDS). This field experiment was carried out as split plot with three replication at the Agricultural Experimental Station, Shahrekord University, Shahrekord, Iran during 2014 and 2015. The objective was to determine the effects of deficit irrigation on dry matter accumulation, mobilization, radiation use efficiency (RUE) and economic RUE (ERUE) of bean genotypes. The results showed that under deficit irrigation conditions, decrease of seed dry matter accumulation was lower in KS21486. The ERUE was decreased in KS21193 under deficit irrigation conditions while ERUE increased under MDS conditions and decreased under SDS conditions in KS21486. The reduction of seed yield under deficit irrigation conditions was more in KS21193 in both years. In conclusion, the genotype KS21486 showed better performance under water deficit condition implying that its seed yield was less susceptible to drought stress conditions. This genotype allocated more dry matter to seeds under water deficit conditions and had higher harvest index, RUE, and ERUE under SDS condition. The results showed that the traits, namely higher ERUE, dry matter allocation to seeds, and HI are suitable indicators to determine drought-resistant genotypes. Abbreviations : NDS: Non-drought stress; MDS: Moderate drought stress; SDS: Severe drought stress; PARi : intercepted PAR: RUE: Radiation use efficiency; ERUE: economic RUE